Prediction the stainless steel sheet fracture with mesh size effect for shell elements. (February 2021) - Wei, Liang; Qin, Fang; Cui, Ke
Abstract: The application of ductile fracture criteria to shell elements yields invalid after the onset of necking and sensitivity to element size. The mesh-size regularisation strain study indicates that fracture strain modified with element dimension results in the same stress state. This phenomenon can't be accurately explained by current strain based fracture models. To fill this gap, this paper proposed that the fracture stress threshold σf for the Mohr-Coulomb criterion can be assumed to be an element dimension effect function of the form: σf ( le ) ∝ le −m . It follows then that the Modified Mohr-Coulomb fracture model and post-initiation damage are related to the element size by stress concentration exponent m . A plasticity and fracture testing program is performed on 1 mm thick 301L steel sheets to test this hypothesis. The Arcan-type tests were employed to calibrate parameters for the damage initiation/fracture model in the equivalent plastic strain-stress triaxial space. The stress concentration exponent m was calibrated by a uniaxial tensile test by using different sizes of a virtual extensometer. At last, the model parameters are validated through a stretch bending test. The comparison of the experimental and FE simulation results demonstrates that the new coupled mesh size effect fracture model can predict stainless steel ductile fracture modelled by large sizes of shell elements with satisfactory accuracy.